Alterações hematológicas e funcionais causadas por venenos de subespécies brasileiras de Crotalus durissus e suas frações isoladas - Souza, Iêda Pereira de (2006)
Venomous snake accidents represent a serious public health problem in tropical countries, as much as for their frequency of occurrence and/or morbidity and mortality that they caused. In Brazil, the genus Crotalus comprise only one species, termed Crotalus durissus, which is divided into six subspecies. The aim of our study was to evaluate the effects promoted by venoms of Crotalus durissus cascavella, originated from the States of Ceará (Cdcc) and Maranhão (Cdcm); C. durissus collilineatus (Cdcol); C. durissus ruruima (Cdru) and its isolated components, such as crotoxin (CTXru) and phospholipase A2 (PLA2ru), in the biological processes of cellular spreading, phagocytosis, hematological alterations and antifungal activity. Male Swiss mice were inoculated intraperitoneally with the venom doses of 120, 50, 27, 20, 10 and 10 µg/Kg, respectively to the snakes described above. After two hours of inoculation blood samples and exudate were collected from orbital plex and peritoneum, respectively. Statistical evaluation was performed using Student-T test with significance level set at 95%. We compared the treated animals with a control group, where animals were inoculated with saline 0.9%. Cdcm and CTXru caused the most severe alterations in the erythrogram. We noticed that 37.5% of the erythrocytes showed macrocytic and microcytic morphology; 25.5% were hipocromic; 25% showed anisocytosis and the presence of polycromasia. We also found Howell Jolly bodies in 16.8% of the examined erythocytes. The total counting of leukocytes was reduced statistically after administration of Cdcc (82.9%), Cdcm (70.1%) and Cdru (83.8%). Cellularity was altered after the inoculation of Cdcc, Cdru and CTXru for all evaluated cells. We noticed a statistic increase of peritoneum total cells caused by Cdcc, Cdcol, Cdru and CTXru. In addition, macrophage was the most predominant cell after peritoneum differential cell counting. However, only Cdcol showed a statistic increase of macrophages (62.3%). We found significant reduction of cellular spreading after administration of all venoms ranging from 52.7 to 65.7%. Phagocytosis was statistically reduced by Cdcc in the periods of 30, 60, 90 and 120 minutes. However, Cdru reduced phagocytosis only at 30, 60 and 90 minutes, Cdcm decreased phagocytosis at 30 and 90 minutes and CTXru in the periods of 60 and 120 minutes. Cdcol and CTXru showed significant fungicide activity against C. albicans in the periods of 30, 60, 90 and 120 minutes, but Cdcc showed similar results at 60, 90 and 120 minutes. We conclude that distinct venoms interfered differently in the intensity of each functional and hematological response. In addition, we postulate that macrophages maybe partially responsible for these alterations. Further studies should be evaluated for the use of venoms as fungicides.